2010
DOI: 10.1590/s1516-80342010000400024
|View full text |Cite
|
Sign up to set email alerts
|

Eletroestimulação neuromuscular na reabilitação da disfagia orofaríngea

Abstract: INTRODUÇÃOA disfagia é uma condição que submete o indivíduo a constante instabilidade clínica, podendo ocasionar complicações como pneumonia aspirativa, desidratação, desnutrição e óbito. Devido a estas questões, este sintoma pode aumentar os custos dos cuidados de saúde com o indivíduo disfágico, bem como prolongar a duração da estada hospitalar (1) . Desta forma, distintas tem sido as propostas para a reabilitação da disfagia orofaríngea pesquisadas ao longo dos anos e discutidas por alguns artigos de revisã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
17
0
5
Order By: Relevance
“…While some studies 1,3,[8][9][10][11][12][13][14][15][16] show benefits in the pathophysiology of swallowing in patients with oropharyngeal dysphagia submitted to NMES, others [5][6][7] report the absence of physiological and functional changes resulting from these stimuli. It must be said that even the publications that demonstrate positive results present questionable methodological designs in scientific relevance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some studies 1,3,[8][9][10][11][12][13][14][15][16] show benefits in the pathophysiology of swallowing in patients with oropharyngeal dysphagia submitted to NMES, others [5][6][7] report the absence of physiological and functional changes resulting from these stimuli. It must be said that even the publications that demonstrate positive results present questionable methodological designs in scientific relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Deglutition disorders lead to the presence of oropharyngeal dysphagia, which can bring clinical problems, such as malnutrition, dehydration and pulmonary complications. In post-stroke patients the main risk factor for the occurrence of aspiration pneumonia is the presence of dysphagia 1 . According to studies, 51% of post-stroke patients present changes in swallowing function in acute phase 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two Brazilian studies literature review with levels of evidence 3A 39,40 They were conducted addressing the applicability and the analysis of the results of the use of NMES in the treatment of oropharyngeal dysphagia. The authors concluded that the efficacy of rehabilitation in oropharyngeal dysphagia with use of electrical stimulation varies from 70% to 80%.…”
Section: Brazilian Studies Of Literature Review On the Applicability mentioning
confidence: 99%